Significance of Chemical Composition Analysis in Urolithiasis (Indian Journal of Public Health Research & Development, 2020)
Introduction: Urolithiasis is the formation of stones in the urinary tract. Between 1% and 15% of peopleglobally are affected by kidney stones at some point in their lives. Knowledge of chemical composition ofRenal stones may be helpful in clinical management of patients as well as in reducing risk of prevalence andrecurrence of stones in this region.Aims and Objectives: To analyse the chemical composition of Urinary tract stones.Material and Method: The present study included 100 uroliths obtained by surgical intervention ofUrolithiasis patients diagnosed at MM Institute of Medical Sciences, MMDU , Mullana from August 2018to October 2019. The powdered form was qualitatively analyzed for their chemical composition adoptingstandard methods.Results: In the present study, out of total 100 patients, the incidence of urolithiasis was more in males(72%) compared to females(28%).Distribution of stones based on their location, showed a high incidenceof stones in the ureter (42%), followed by Bladder (26%) and Urethra (19%). Calcium oxalate was the mostpredominant chemical composition in the stones analyzed (63%), followed by Uric acid (18%). Calciumcarbonate, Calcium phosphate and Magnesium Ammonium phosphate were predominant in 8%, 6% and 5%of stones respectively.Conclusion: Analysis of the chemical composition of stones and knowledge of its etiology will help inimproving the management of patients with Urolithiasis.
Keywords: Urolithiasis; Chemical; Ureter; Calcium; Oxalate